84.0k views
2 votes
F(x)= 3x-27/14
Find f(f^-1(241))

User TusharJ
by
7.7k points

2 Answers

4 votes
Okay, the f^-1 means we need to invert the original function. So switch x's and y's and solve for y.
y = 3x - 27/14
x = 3y - 27/14
-3y = -x - 27/14
y = 1/3x + 9/14
Then plug in 241
y = 80 1/3 + 9/14
y = 80 41/42

Now you have to plug it back into the original function.
So:
y = 3(80 41/42) - 27/14
y = 3401/42 - 27/14
y = 79.0476190476 or 79 and 1/21
User Mosheh
by
7.3k points
3 votes

Answer:

241

Explanation:

User Sourya Dey
by
7.1k points